RESEÑA de: Torrente Ballester, Gonzalo. Crónica del rey pasmado (Edición de Carmen Becerra Suárez). Madrid : Akal, 2012. - Pérez Álvarez, David (Signa: Revista de la Asociación Española de Semiótica, 2014)
-